Variation in body composition in professional soccer players: Interseasonal and intraseasonal changes and the effects of exposure time and player position - Carling, C.; Orhant, E. (The Journal of Strength and Conditioning Research, 2010)
The aim of this study was to examine variations in measures of body composition in elite soccer players. Skinfolds and measures of body mass (BM) recorded on a monthly basis across an entire competitive season in a group of senior professional players (n = 26) were used to estimate percentage body fat (%BF) and provide fat-free body mass (FFBM) values. Mean values in players were compared between 6 specific positional roles (goalkeepers, central and lateral defenders/midfielders and center-forwards). In-season variations in measures were studied by comparing values at 5 separate points across the season. The effects of positional group (goalkeepers, defenders, midfielders, and forwards) and exposure time to play (participation time in training and matches) in relation to in-season variations were also examined. To investigate interseasonal changes, repeated measures were taken in players (n = 9) over 3 consecutive seasons. In relation to positional role, a difference in average %BF and BM values was observed (p < 0.001), with substantial differences observed in goalkeepers, lateral midfielders, and forwards. Across all players, there were significant in-season variations in %BF (between start- and mid-season and mid- and end-season, p < 0.001) and FFBM (between start- and mid-season and start- and end-season, p < 0.001), whereas BM remained unchanged. Further analysis of these fluctuations in %BF and FFBM at different points of the season showed that variations differed across the positional groups (p < 0.01), especially in defenders and midfielders. In contrast, no association was observed between measures and exposure time and no differences were reported across seasons. Practitioners should consider individual positional role when interpreting mean body composition data. They should also take into account positional groups when in-season variations in body composition are identified.